Measures for the development and propagation of the Filipino language - Yamio, Teodora Matias 1927- ([Quezon City s.n.], 1959)
This paper presents a study of the measures adopted in the past for the development and propagation of the Filipino Language. A study of these measures may point to a new and better approach to give impetus to the national language project.
Bibliography: l. [134]-142.
Mimeographed
Thesis (M.Ed.)--University of the Philippines, 1959
Vita
Keywords: Tagalog language -- Study and teaching